Comparative analysis of Brazilian medical and dental ethics codes - Carvalho de Melo, Allan Ulisses; Rodrigues Jacinto Gonçalves, Suzane; Ferreira Ribeiro, Cyntia; de Santana Santos, Thiago; Ribeiro de Santana, Augusto Tadeu (Acta Bioethica, 2012)
Professional ethics codes are norms (federal authority resolutions) prepared by members of the different categories of workers with the goal to guide the ethical conduct of these professionals in relation to patients, colleagues and society. The aim of this study was to carry out a comparative analysis of ethical codes in Dentistry and Medicine. It was observed that differences between these documents were due more to the particularities of each profession than to different focus, facing similar problems. It was concluded that Dentistry and Medicine ethical codes have more points in common than differences, but it would be interesting that Class Advisory Committees, when proposing actualizations and changes to their current codes, they will look what other health care professions view as deontological norms, with the end to have into account aspects which may be important also for their professional class, in order to extend the codes and facilitate to physicians and dentists ethical decision making in their daily task in benefit to the health of human beings and community.